Cryptic persistence and loss of local endemism in Lake Constance charr subject to anthropogenic disturbance - Baer, Jan; Schliewen, Ulrich K.; Schedel, Frederic D. B.; Straube, Nicolas; Roch, Samuel; Brinker, Alexander (Ecological applications, 2023)
In the welcome circumstance that species believed extinct are rediscovered, it is often the case that biological knowledge acquired before the presumed extinction is limited. Efforts to address these knowledge gaps, in particular to assess the taxonomic integrity and conservation status of such species, can be hampered by a lack of genetic data and scarcity of samples in museum collections. Here, we present a proof‐of‐concept case study based on a multidisciplinary data evaluation approach to tackle such problems. The approach was developed after the rediscovery, 40 years after its presumed extinction, of the enigmatic Lake Constance deep‐water charr Salvelinus profundus. Targeted surveys led to the capture of further species and additional sympatric normal charr, Salvelinus cf. umbla. Since the lake had been subject to massive stocking in the past, an evaluation of the genetic integrity of both extant forms was called for in order to assess possible introgression. A two‐step genomic approach was developed based on restriction site associated DNA (RAD). Diagnostic population genomic (single nucleotide polymorphism [SNP]) data were harvested from contemporary samples and used for RNA bait design to perform target capture in DNA libraries of archival scale material, enabling a comparison between extant and historic samples. Furthermore, life history traits and morphological data for both extant forms were gathered and compared with historical data from the past 60–120 years. While extant deep‐water charr matched historical deep‐water specimens in body shape, gill raker count, and growth rates, significant differences were discovered between historical and extant normal charr. These resulted were supported by genomic analyses of contemporary samples, revealing the two extant forms to be highly divergent. The results of population assignment tests suggest that the endemic deep‐water charr persisted in Lake Constance during the eutrophic phase, but not one of the historical genomic samples could be assigned to the extant normal charr taxon. Stocking with non‐endemic charr seems to be the most likely reason for these changes. This proof‐of‐concept study presents a multidisciplinary data evaluation approach that simultaneously tests population genomic integrity and addresses some of the conservation issues arising from rediscovery of a species characterized by limited data availability.